2014
DOI: 10.1021/es5012548
|View full text |Cite
|
Sign up to set email alerts
|

Humic Acid Acts as a Natural Antidote of Graphene by Regulating Nanomaterial Translocation and Metabolic Fluxes in Vivo

Abstract: Graphene-related research has intensified rapidly in a wide range of disciplines, but few studies have examined ecosystem risks, particularly phytotoxicity. This study revealed that graphene significantly inhibits the number of wheat roots and the biosynthesis of chlorophyll, and altered the morphology of shoots. Humic acid (HA), a ubiquitous form of natural organic matter, significantly (P < 0.05) relieved this phytotoxicity and recovered the sharp morphology of shoot tips. Both graphene and graphene-HA were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
46
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(51 citation statements)
references
References 44 publications
5
46
0
Order By: Relevance
“…As an emergent nanomaterial, although the related applications of graphene are rapidly increasing, the current or future concentrations of graphene in the environment have not been determined. Hence, to be comparable with the doses of graphene used in previous phytotoxicity studies [7,8] and combined according to the US EPA toxicity studies on the food crops which commonly carried out at high concentrations (2000-5000 mg L −1 ) of the nanoparticles [14,15], the exposed graphene was prepared at 0-1500 mg L −1 in present study.…”
Section: Graphene Properties and Characterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…As an emergent nanomaterial, although the related applications of graphene are rapidly increasing, the current or future concentrations of graphene in the environment have not been determined. Hence, to be comparable with the doses of graphene used in previous phytotoxicity studies [7,8] and combined according to the US EPA toxicity studies on the food crops which commonly carried out at high concentrations (2000-5000 mg L −1 ) of the nanoparticles [14,15], the exposed graphene was prepared at 0-1500 mg L −1 in present study.…”
Section: Graphene Properties and Characterizationmentioning
confidence: 99%
“…Begum [7] suggested the negative effects of graphene, wherein the growth of leaves of cabbage, tomato, and red spinach plants was inhibited after 20 days of treatment with 500-2000 mg L −1 graphene. Decreasing the concentration of graphene (200 mg L −1 ) for 5 days did not have significant adverse effects on seed germination, root length, or fresh weight of wheat plants [8]. Wang [9] and Zhao [10] showed that GO exposure in the g L −1 range for 8 days did not alter germination, seed development, or shoot and root growth in Arabidopsis plants.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…Meanwhile more investigations reported that nanopaticles had no effect on germination but did influence the growth of plants. For example, graphene had no obvious effects on wheat seed germination, whereas decreaseed the number of wheat roots [9]. CuO nanoparticles have no effects on maize seeds germination, while inhinited the root elongation [10].…”
Section: Introductionmentioning
confidence: 98%
“…Previous research report the influence of humic acid (HA) on toxicity of TiO 2 NPs toward developing zebrafish, indicating that adsorption of HA increased suspensions stability and decreased TiO 2 NPs exposure, and TiO 2 NPs showed higher toxicity in the presence of HA (Yang et al 2013). Moreover, it has been proved that HA can increase the surface negative charges and reduce the aggregation of graphene, and then regulate (Hu et al 2014). Besides, media ionic strength yields visible toxicity of gold nanoparticles to embryonic zebrafish, suggesting that low ionic media induce morbidity and mortality but high ionic media hardly cause biological response (Truong et al 2012).…”
Section: Introductionmentioning
confidence: 99%